Surgical and demographic trends in genital gender-affirming surgery in transgender women: 40 years of experience in Amsterdam. Issue 1 (19th July 2021) - van der Sluis, W B; de Nie, I; Steensma, T D; van Mello, N M; Lissenberg-Witte, B I; Bouman, M -B
Abstract : This was a single-centre, retrospective study of transgender women undergoing genital gender-affirming surgery. A chart study was conducted, recording individual demographics, all genital surgical procedures, and surgical techniques. Procedure incidence, techniques employed, and demographic variations over the years were analysed.